Specifications and field of application of fire hoses with an inner diameter of 38 mm - Grachulin Александр; Kamlyuk Андрей; Korsakov Максим; Navrotskiy Олег; Romanenko Янина (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
The authors propose the experimental setups for research hydraulic losses in the hose line and the total capacity of fire hoses Describes technique of research. Experimentally determined pressure loss in the hose line having an inner diameter of 38 mm for the flow of water, solution of water with foaming agent, foam. Determine the total capacity of the hose with an inner diameter of 38 mm.